Meat Productivity and Sexual Differentiation of New Zealand White Breed Rabbits - Bakhtiyorovich, Ibragimov Bahodir; Sherkulovich, Ismailov Mirzakul (International Journal of Psychosocial Rehabilitation, 2020)
This article presents materials on the study of feed conversion depending on the age and gender of New Zealand white rabbit breeds from one month to twelve weeks. For the experiment, 30-day-old females and males of 10 animals were selected. Two groups were formed, in which the first group contained females, and the second males in the same condition and feeding. After 84 days of age, rabbits were slaughtered for meat as a broiler. Differences in meat quality, live and slaughter weight, raw fat mass, and slaughter yield of rabbits in groups were studied. The morphological structure of the carcasses was compared.